Comparison of Inflammation Parameters in the Elderly and Adults to the Outcomes of Confirmed Covid-19 Patients - Pradana Maulana Putra; Ali Assagaf; Mohammad Isa (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
The elderly is susceptible to infection due to immunosenescence causing high cases of infection with significant deaths due to Coronavirus Disease 2019 (COVID-19) pandemic. Many studies have examined inflammatory parameters as predictors of the outcome of COVID-19 cases, but there has been no comparison of the values of these parameters between the elderly and adult groups. This study aims to explain the relationship between inflammatory parameter values in the elderly group compared to the adult group with the outcome of confirmed COVID-19 patients treated at Ulin Hospital Banjarmasin. An analytical observational cross-sectional design study with the samples was patients with examined Neutrophil-Lymphocyte Ratio (NLR), Platelet-Lymphocyte Ratio (PLR), Erythrocyte Sedimentation Rate (ESR), and C-reactive protein (CRP) when admitted to the COVID-19 isolation room at Ulin Banjarmasin Hospital and was divided into elderly and adult groups. A bivariate correlation test was conducted to assess the relationship between each parameter and continued by finding the cut-off value using the Receiver Operating Characteristic (ROC) curve. Odds Ratio (OR) is sought to find out how much the outcome risk prediction is based on the cut-off value. The relative coefficients of NLR, PLR, CRP, and ESR in the elderly group of 1147 subjects were 0.304; 0.119; 0.378; and 0.071. While the cut-off value of NLR, PLR, CRP, and ESR for the elderly group is 6.77; 257.5; 95.65, and 53.4. Outcomes prediction of the confirmed COVID-19 patients in the elderly group from the most significant are CRP, NLR, and PLR. Meanwhile, ESRs are statistically insignificant. The results showed that there are differences in inflammatory parameter values between the elderly and adult groups to predict the outcome of COVID-19 cases.